Partisipasi Masyarakat Dalam Kelompok Kegiatan (Poktan) Kampung Keluarga Berkualitas di Desa Penarungan, Kecamatan Mengwi, Kabupaten Badung - Ni Putu Anjelina; Lilik Antarini; Nyoman Sumawidayani (Faculty of Social and Political Science, 2024)
Quality Family Villages (Kampung KB) aim to improve the quality of Human Resources by emphasizing strengthening family and community institutions. In an effort to realize this goal, active community participation is needed in various existing activity groups (Poktan). Community participation in Poktan BKB, BKR, and BKL has reached 100%, while the other two Poktan, namely PIK-R, amounted to 5.69% and UPPKA with the lowest percentage, only 2.88%. This research aims to determine community participation in the Quality Family Village activity group (Poktan) in Penarungan Village, Mengwi District, Badung Regency. This research uses a qualitative descriptive research approach, with data collection techniques through observation, interviews and documentation. The unit of analysis in this research was 14 informants consisting of the Head of Penarungan Village, Chair of the Penarungan Village KB Village Working Group, Penarungan Village KB Village Extension Officer, KB Village Poktan Cadre, and Community Members of the KB Village Poktan. Community participation in this research is assessed from participation during decision making, implementation, receiving benefits, and evaluation. The results of the research show that community participation in the Quality Family Village Poktan in Penarungan Village is still not optimal. At the implementation stage, community participation only took part in activities that were integrated with Poktan so that PIK-R and UPPKA Poktan had a low percentage of participation because integrated activities also had low participation. There are several obstacles that hinder community participation, such as low public awareness, minimal funding for Poktan, and limited data.